2017
DOI: 10.19080/ctoij.2017.04.555637
|View full text |Cite
|
Sign up to set email alerts
|

Bone Metastases: An Overview

Abstract: Bone is a frequent site of metastases and typically indicates a short--term prognosis in cancer patients. Once cancer has spread to the bones it can rarely be cured, but often it can still be treated to slow its growth. The majority of skeletal metastases are due to breast and prostate cancer. Bone metastasis is actually much more common than primary bone cancers, especially in adults. The diagnosis is based on signs, symptoms and imaging. New classes of drugs and new interventions are given a better quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
206
0
14

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(225 citation statements)
references
References 53 publications
5
206
0
14
Order By: Relevance
“…"Exposure of carcinoma cells to NPC-conditioned medium isolated soluble factors contributing to outgrowth" [15]. "We recently showed that the simultaneous targeting of glucose and glutamine under calorie restriction could signi icantly reduce systemic metastatic cancer in the VM-M2 mouse model" [17]. "The liver is a highly metastasis-permissive organ" [20].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…"Exposure of carcinoma cells to NPC-conditioned medium isolated soluble factors contributing to outgrowth" [15]. "We recently showed that the simultaneous targeting of glucose and glutamine under calorie restriction could signi icantly reduce systemic metastatic cancer in the VM-M2 mouse model" [17]. "The liver is a highly metastasis-permissive organ" [20].…”
Section: Discussionmentioning
confidence: 99%
“…"NPCs in the metastatic hepatic niche secrete factors that can induce a partial mesenchymal shift in epithelial breast cancer cells thus initiating outgrowth, and that this is in part mediated by EGFR Epidermal growth factor receptor activation" [15]. "The microenvironment must be favorable for tumor cell survival" [17]. "The bone formation and reabsorption release and activate survival and growth promoting factors that may contribute to bone metastases development" [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations